Combining plasma p-tau217 and cross-cultural cognitive tests to identify Alzheimer's Disease in an ethnically diverse mixed memory clinic cohort - Kjaergaard, Daniel; Simonsen, Anja Hviid; Stomrud, Erik ; 0000-0002-0841-5580; Bali, Divya; Janelidze, Shorena; Hansson, Oskar ; 0000-0001-8467-7286; Waldemar, Gunhild; Nielsen, T. Rune (Journal of the Neurological Sciences, 2025)
Objective: To determine whether combining routine cross-cultural cognitive assessments with plasma phosphorylated tau217 (p-tau217) increases diagnostic accuracy in identifying Alzheimer's disease (AD) in a consecutive mixed memory clinic cohort of ethnically diverse patients. Methods: We included 201 memory clinic patients originating from 42 different countries. Patients were examined with the Multicultural Cognitive Examination (MCE) as part of their routine cognitive assessment. Plasma p-tau217 levels were analyzed blinded to the results of the clinical evaluation. Repeated cross-validated models assessed the added diagnostic value of plasma p-tau217 through change in accuracy metrics, including sensitivity, specificity, predictive values, and likelihood ratios. The primary outcome was clinically established AD. In subgroup analyses, accuracy metrics were evaluated for differentiating AD from other dementia disorders and patients with and without AD pathology determined by cerebrospinal fluid biomarkers or Amyloid-β PET. Results: Routine cognitive assessment with the MCE alone demonstrated high diagnostic accuracy for identifying AD (AUC: 0.80–0.81). However, combining the MCE with plasma p-tau217 significantly increased diagnostic accuracy (AUC: 0.91–0.93), which mainly reflected an increased ability to rule-out AD. When differentiating AD from other dementia disorders, the MCE alone was less accurate (AUC: 0.64–0.65), and accuracies increased by including plasma p-tau217 (AUC: 0.85–0.89). Conclusions: Combining routine cross-cultural cognitive tests with an accurate plasma biomarker increased the accuracy of identifying AD in a diverse mixed memory clinic cohort. These results demonstrate the value of using appropriate diagnostic tools in culturally, linguistically, and ethnically diverse patients, who are known to face barriers in their clinical evaluation.
Publisher Copyright: © 2025 The Authors
Keywords: Alzheimers disease; diversity; ethnicity; Neuropsychological test; phosphorylated tau; plasma biomarkers